Resource box for resilient seed systems: handbook - Vernooy, Ronnie; Bessette, Guy; Rudebjer, P.G.; Otieno, G. (Bioversity International, 2016)
The resource box for resilient seed systems, developed by a multidisciplinary team of Bioversity International researchers, is a tool that supports research and capacity building on resilient seed systems in the context of adaptation to climate change. The eight modules of the box represent eight steps of a participatory research cycle from situational analysis to knowledge sharing and communication. The handbook complements the online version which can be found at: http://www.seedsresourcebox.org